2020
DOI: 10.1063/1.5136093
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical equations of motion method based on Fano spectrum decomposition for low temperature environments

Abstract: The hierarchical equations of motion (HEOM) method has become one of the most popular methods for the studies of the open quantum system. However, its applicability to systems at ultra-low temperatures is largely restrained by the enormous computational cost, which is caused by the numerous exponential functions required to accurately characterize the non-Markovian memory of the reservoir environment. To overcome this problem, a Fano spectrum decomposition (FSD) scheme has been proposed recently [Cui et al., J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 104 publications
0
35
0
Order By: Relevance
“…[62,63,77,78], the HEOM method has been extended to arbitrary spectral density function as well as finite temperature environment situation. Moreover, it has been reported that the HEOM method can be extended to simulate the dissipative dynamics of a few-level system embedded in a fermionic environment [53,65,79] or a spin environment [80,81]. It would be very interesting to extrapolate our study to these more general situations.…”
Section: Discussionmentioning
confidence: 99%
“…[62,63,77,78], the HEOM method has been extended to arbitrary spectral density function as well as finite temperature environment situation. Moreover, it has been reported that the HEOM method can be extended to simulate the dissipative dynamics of a few-level system embedded in a fermionic environment [53,65,79] or a spin environment [80,81]. It would be very interesting to extrapolate our study to these more general situations.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the properties of the impurity, the hierarchical equations of motion (HEOM) approach [65][66][67][68][69][70] is employed, which takes the reduced density matrix of the system ρ and a hierarchical set of auxiliary density operators as the basic variables. The HEOM theory is, in principle, formally exact, and its numerical outcomes are guaranteed to be quantitatively accurate if the results converge with respect to the truncation tier of the hierarchy.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative numerical exact bench-marking approach is the hierarchical equations of motion (HEOM) [44][45][46][47][48][49][50][51][52][53] approach pioneered by Tanimura and Kubo. 54 HEOM approach captures the combined effects of system-environment dissipation, non-Markovian memory effect, and many-body correlation in a non-perturbative manner.…”
Section: Introductionmentioning
confidence: 99%